From bureaucracy to e-Government: Digital transformation of Public Administration in Romania for a sustainable future - BURLACU, Sorin; DOBRE, Florin; MATEESCU, Vicențiu-Mihai; ANDREI, Ionuț-Valeriu (European Journal of Sustainable Development, 2025)
The digital transformation of public administration is an essential pillar for modernizing and streamlining public services, contributing to a sustainable future. Romania has adopted ambitious strategies for digitalization, aligning with European initiatives such as the Digital Compass 2030 and using tools such as the National Recovery and Resilience Plan. However, progress is uneven, and Romania consistently ranks last in the European digitalization rankings (DESI). This research aims to investigate how public administration in Romania is evolving towards e-government, analyzing the policies, strategies and determinants of this process, to identify the main challenges and opportunities associated with the digitalization of the public sector. The methodology used is based on comparative analysis of public policies and secondary analysis of existing data, examining strategic documents, international reports and relevant national initiatives. Strategic documents (SNDCIDR, PNRR), international reports (DESI, Eurostat) and national initiatives (Ghi?eul.ro, e-government hubs) are examined to highlight progress, bottlenecks and lessons learned. A SWOT analysis is also carried out to identify the strengths and weaknesses of the digitalization of public administration in Romania, correlated with the opportunities and threats in the European context. The results suggest that, although there is a strategic framework and significant funding, the lack of clear coordination, the insufficiently adapted legislative framework and the low degree of adoption of digital services by the population and SMEs remain major challenges. The study provides a critical perspective on the factors that facilitate or hinder the transition to e-government and proposes directions for strengthening the digital transformation in Romanian public administration. Keywords: digital administration, e-government, public policies, digitalization, Romania, sustainability